PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN PPKN KELAS X IPS 3 SMAN 8 MUARO JAMBI: PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN PPKN KELAS X IPS 3 SMAN 8 MUARO JAMBI - Tiara, Ernita Dita; Anderson, Irzal; Ichsan, Muhammad (Prodi PPKn Universitas Slamet Riyadi, 2023)
The purpose of this study was to increase student learning independence in Civics subjects by applying the contextual teaching and learning (CTL) learning model in class X IPS 3 SMA Negeri 8 Muaro Jambi. This type of research is Classroom Action Research (PTK) with a research design using the Kemmis & Taggart spiral model. The research was carried out in 3 cycles where each cycle consisted of 3 meetings. Each cycle is carried out through 4 stages of activity, namely planning, implementing actions, observing (observation), and reflecting. The success criterion set in the research is 60%. The results showed that in cycle I the level of student learning independence increased from the initial condition of an average value of 23% to 49% but had not yet reached the established success criteria. Cycle I then made improvements to continue in cycle II. After the repairs were made, there was an increase in cycle II which increased by 9% to 58% but also did not reach the specified success criteria. Improvements were made again in cycle II to be continued in cycle III. The results of the research cycle III increased by 11% to 69%, which means that the action was declared successful because it had achieved the specified success criteria.Keywords: Independent Learning, CTL Learning Model